A multidisciplinary approach to a unique palaeolithic human ichnological record from Italy (Bàsura cave) - Romano, Marco (2019)
Based on the integration of laser scans, sedimentology, geochemistry, archeobotany, geometric morphometrics and photogrammetry, here we present evidence testifying that a Palaeolithic group of people explored a deep cave in northern Italy about 14 ky cal. BP. Ichnological data enable us to shed light on individual and group level behavior, social relationship, and mode of exploration of the uneven terrain. Five individuals, two adults, an adolescent and two children, entered the cave barefoot and illuminated the way with a bunch of wooden sticks. Traces of crawling locomotion are documented for the first time in the global human ichnological record. Anatomical details recognizable in the crawling traces show that no clothing was present between limbs and the trampled sediments. Our study demonstrates that very young children (the youngest about 3 years old) were active members of the Upper Palaeolithic populations, even in apparently dangerous and social activities.